Trasformasi nilai sosial melalui pendidikan formal di era digital - Azizah, Putri Nurul; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research intends to examine the shifts in social values brought about by formal education in the digital age, where advancements in information and communication technology profoundly influence the learning experience. This change necessitates the incorporation of technology in education, focusing on enhancing social values as a basis for developing students' character. The research utilizes a qualitative descriptive approach by reviewing 10 Indonesian scientific articles published in the past five years. Data were gathered and thematically examined to determine the influence of digital literacy, curriculum technology integration, and government policies in facilitating the change of social values. The findings indicate that digital literacy plays a crucial role in enhancing social values, whereas the effectiveness of technology integration largely relies on teacher skills, infrastructure access, and appropriate policy backing. This research advocates for continuous training for teachers and fair access to technology to guarantee the successful transition to digital education, addressing both technological aspects and the effective maintenance of social values and norms. The results are anticipated to act as a guide for policymakers and education practitioners in enhancing the role of technology in formal education to create generations that are both digitally proficient and have a robust social character